Caenorhabditis elegans como modelo experimental para estudos toxicológicos e farmacológicos dos extratos de Luehea divaricata e Paullinia cupana - Arantes, Leticia Priscilla (2016)
The nematode Caenorhabditis elegans is a valuable tool for toxicological and pharmacological studies. Despite its simple body, the most part of its genes and signaling pathways are similar to humans, and alterations in behaviors may be related to specif neuronal circuits Plant extracts might be useful in Medicine, however few species were studied. Thus, Herein, toxicological and pharmacological effects of the ethanolic extract of Luehea divaricata and the potencial effects of the ethanolic extract of Paullinia cupana seeds on aging and methylmercury (MeHg)-induced toxicity were investigated in C. elegans. L. divaricata extract showed antioxidant activity against different prooxidants in vitro and in C. elegans in a different manner. C. elegans allows antioxidant studies in a whole organism with a biological situation of oxidative stress. L. divaricata extract also increased nematode pharynx pumping rate through anticholinesterasic activity and showed a higher pharmacological potencial when compared to its isolated compound (rutin), probably due to synergic effects of its compounds. P. cupana extract extended nematode’s lifespan and healthspan in a DAF-16/FOXO and HSF-1 dependent manner, signaling pathways involved in upregulation of genes associated to longevity and stress resistance. This effect was accompanied by a reduction in intestinal lipofuscin and in the number of protein aggregates. Genes modulated by GEE included gst-4, hsf-1 and skn-1. Furthermore, this study demonstrated that purinergic signaling might be a therapeutic target to modulate aging. P. cupana extract also exerted neuroprotective effects against MeHg, increasing worm survival and decreasing behavior impairments in skn-1(ok2315) strain, which is deficient in detoxification and oxidative stress response. The extract conducted skn-1(ok2315) worms to a faster recover and progress in development, at least in part, through upregulation of genes related to metal transport (aat-2) and detoxification (mtl-1 e mtl-2), and antioxidant response (sir-2.1 and sod-3), resulting in faster and more efficient cellular repairs. C. elegans allowed simple analyzes of the mechanisms involved in extract’s effects and directed further studies.